Fluorescence resonance energy transfer based quantitative analysis of feedforward and feedback loops in epidermal growth factor receptor signaling and the sensitivity to molecular targeting drugs. (9th June 2014) - Fujita, Yoshihisa; Komatsu, Naoki; Matsuda, Michiyuki; Aoki, Kazuhiro
<x xml:space="preserve">Abstract</x> The Ras‐ERK and PI3K‐mTOR pathways are hyperactivated in various malignant tumors. Feedforward (FF) and feedback (FB) regulations between the Ras‐ERK and the PI3K‐mTOR pathways have been suggested to attenuate sensitivity to drugs targeting these pathways and confer tumor resistance to therapies. However, because analyses of such regulations require measurements and perturbations with high temporal resolution, the quantitative roles played by FF and FB regulations in the intrinsic resistance to molecular targeting drugs still remain unclear. To address this issue, we quantified FF and FB regulations of the epidermal growth factor receptor (EGFR) signaling pathway by Förster/fluorescence resonance energy transfer (FRET) imaging. EGF‐induced activation of EGFR, Ras, extracellular‐signal‐regulated kinase and S6K with or without inhibitors was measured by FRET imaging, and analyzed by semi‐automatic image processing. Based on the imaging data set and kinetic parameters determined by our previous studies, we identified the roles played by a coherent FF regulation and two negative FB regulations, one of which was not recognized previously. The systems analyses revealed how these FF and FB regulations shape the temporal dynamics of extracellular‐signal‐regulated kinase activity upon EGF stimulation. Furthermore, the simulation model predicts the response of molecular targeting drugs applied solely or in combination with each other to BRaf‐ or KRas‐mutated cancer cell lines, indicating the validity of a quantitative model integrating FF and FB regulations. Database The mathematical model described here has been submitted to the JWS Online Cellular Systems Modelling Database and can be accessed free of charge at http://jjj.mib.ac.uk/webMathematica/UItester.jsp?modelName=fujita